Error analysis in French simple sentence writing among the students of UniKL MFI - Abdul Karim, Shobehah; Subramaniam, Vijayaletchumy; Abdul Halim, Hazlina (Human Resources Management Academic Research Society (HRMARS), 2024)
This study on learning French as a foreign language (FL) focuses on French writing skills. Learning FL requires the student to master communication skills as well as writing skills. Good command of basic French grammar may help for better writing skills for the target language. This study is limited to simple French sentence writing skills among students by analysing errors in their writing. The study respondents comprised of 50 French 1 (WFD10101) students from University Kuala Lumpur Malaysia France Institute (UniKL MFI). The research data was analysed both qualitatively and quantitatively. The research location was UniKL MFI. This document analysis study used essays from the answer script of section A, question 11 of the French 1 final test. The results of the students’ writing were analysed through Taxonomy of Errors by Dulay, Burt and Krashen (1982) to identify the students’ errors in constructing simple French sentences. The findings of this research showed students had the tendency to make errors in using prepositions, followed by verbs, nouns, and adjectives. These errors occurred as the students lack basic French grammatical knowledge. In addition, with the status of French as a FL in Malaysia, there are differences in terms of grammar and sentence structures between French and Bahasa Malaysia. Therefore, these are the factors that cause the respondents to make mistakes errors when writing and subsequently perform errors in adding, reducing, and selecting in French sentences. Hopefully, this research will be beneficial for the learners and teachers of French language in Malaysia.